2014
DOI: 10.1155/2014/714271
|View full text |Cite
|
Sign up to set email alerts
|

Short and Long Term Outcomes Associated with Fetal Cholelithiasis: A Report of Two Cases with Antenatal Diagnosis and Postnatal Follow-Up

Abstract: The aims of this study were to present and discuss ultrasound findings of prenatal fetal cholelithiasis in two cases with different etiology and evolution. Case 1: a pregnant woman from sub-Saharan Africa, suffering from Lyme disease, was treated with ceftriaxone sodium. Six weeks later, biliary sludge associated with polyhydramnios was detected in the fetus and the fetal growth percentile was 14. Emergency caesarean was performed at 36 weeks of gestation due to fetal distress. Biliary sludge persists in the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 14 publications
(17 reference statements)
0
17
0
1
Order By: Relevance
“…9 These may be related to a high degree of morbidity and mortality. 9,10,12 In special situations, such as when the gallbladder is contracted, differentiation between them may prove to be very difficult. 10 Calcifications in the fetal liver are a relatively more common finding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 These may be related to a high degree of morbidity and mortality. 9,10,12 In special situations, such as when the gallbladder is contracted, differentiation between them may prove to be very difficult. 10 Calcifications in the fetal liver are a relatively more common finding.…”
Section: Discussionmentioning
confidence: 99%
“…4 Troyano-Luque J et al mentioned in his case report that many gallstones resolve spontaneously in-utero, soon after birth or within 6 months and persistence of gall stones after 1 year results in cholelithiasis in childhood and beyond. 12 Two hypotheses have been proposed for the disappearance of fetal gallstones-(a) spontaneous passage of gallstones during early neonatal period; or (b) dilution of cholesterol crystals with postnatal hydration. Rarely they may persist even after 6 months of age and may require treatment with Ursodeoxycholic acid.…”
Section: Discussionmentioning
confidence: 99%
“…Ceftriaxone is known to enhance the precipitation of insoluble calcium salts, which is a predisposing factor for cholelithiasis [32]. During pregnancy, the transplacental passage of ceftriaxone could produce the same effect on the fetal gallbladder, inducing gallstone formation [31]. Conditions associated with raised maternal estrogen and progestin levels (e. g., twin pregnancy) could predispose the patient to FC as a result of increased cholesterol secretion and the reduction of biliary acids synthesis [11,14,25].…”
Section: Discussionmentioning
confidence: 99%
“…A maternal history of gallstones has been observed in 7 cases, suggesting a possible genetic predisposition to cholelithiasis [11,14,18]. In addition, maternal diabetes [14,24], prostaglandin use [4], prenatal fetal leukomoid reaction [4], chromosomal aberrations [4], intrauterine growth restriction [3, 4, 13-15, 17, 27], amniotic fluid disorders [4,7,13,14,17,24,25,31], and different cardiac, gastrointestinal, and urologic malformations [4,7,13,14] have been observed in association with FC, but no clear correlation has been proposed. Some authors have suggested that FC may be sex-linked [7,11,18,26,31].…”
Section: Discussionmentioning
confidence: 99%
“…대부분의 태아 담석증은 무증상이며 심각한 합병증을 초래하는 경우는 드물지만, 간혹 소아 또는 성인기의 담석증 및 담 낭염으로 이환되기도 하며 13) , 만성 담석증과 동반된 총담관폐쇄, 만성 담낭염으로 신생아기에 복강경 담낭절제술을 시행받은 증례 도 있다 14) . …”
unclassified